2014
DOI: 10.1186/preaccept-1965461416135619
|View full text |Cite
|
Sign up to set email alerts
|

Chronic multisite pain in major depression and bipolar disorder: cross-sectional study of 149,611 participants in UK Biobank

Abstract: BackgroundChronic pain has a strong association with major depressive disorder (MDD), but there is a relative paucity of studies on the association between chronic multisite pain and bipolar disorder (BD). Such studies are required to help elucidate the complex biological and psychological overlap between pain and mood disorders. The aim of this study is to investigate the relationship between chronic multisite pain and mood disorder across the unipolar-bipolar spectrum.MethodsWe conducted a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 15 publications
5
41
0
Order By: Relevance
“…Disorders of the CNS were associated with the greatest pain spread categories (i.e., RP-Heavy and WSP). These results are consistent with data obtained in cross-sectional and review studies that linked those comorbidities with the development and/or maintenance of WSP 11,16,23,24,27,33,4042,52,53. The observed strong relationship between those comorbidities and the pain categories can be partly explained by the fact that greater levels of spreading of pain trigger a tendency in health-seeking behavior more frequently than the more limited spreading of pain 24.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Disorders of the CNS were associated with the greatest pain spread categories (i.e., RP-Heavy and WSP). These results are consistent with data obtained in cross-sectional and review studies that linked those comorbidities with the development and/or maintenance of WSP 11,16,23,24,27,33,4042,52,53. The observed strong relationship between those comorbidities and the pain categories can be partly explained by the fact that greater levels of spreading of pain trigger a tendency in health-seeking behavior more frequently than the more limited spreading of pain 24.…”
Section: Discussionsupporting
confidence: 91%
“…Spatial categories of pain used clinically are local pain (LP), regional pain (RP), and WSP 31,32. A recent epidemiological study found that the vast majority of patients with pain had a regional pain condition; the study also suggested that future analyses should split this group into two categories, an approach used by a large study from the United Kingdom 33. Few studies have investigated the prevalence of pain spread categories in the elderly, and even fewer studies have performed in-depth analyses of the associations of pain spread 1,10,15,16,34,35…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that 59% of people had pain at more than two sites in our population‐based cohort with a mean age of 63 years . Epidemiological studies have shown that multisite pain (MSP) is linked to worse health outcomes as compared with single‐site pain, including poorer physical health, worse health‐related quality of life, more severe depressive symptoms, cognitive impairments, and poorer sleep quality …”
Section: Introductionmentioning
confidence: 89%
“…Psychological distress plays a significant role in the pain experience and is an experiential factor in the population with chronic pain (Finan & Smith, ; Yalcin & Barrot, ). Indeed, pain is associated with depression (Kroenke et al., ; Ligthart et al., ; Zakoscielna & Parmelee, ), is prevalent in depressed people (Failde et al., ; Nicholl et al., ) and, in fact, has a non‐recursive (reciprocal) relationship with depression (Chou, ; Kroenke et al., ; Meyer, Cooper, & Raspe, ). Similarly, pain has been associated with anxiety (Beesdo et al., ; El‐Gabalawy, Mackenzie, Shooshtari, & Sareen, ; Smeijers et al., ) and sleep disturbance (Schrimpf et al., ; Schuh‐Hofer et al., ; Sivertsen et al., ; Smith, Edwards, McCann, & Haythornthwaite, ).…”
Section: Introductionmentioning
confidence: 99%